Comparison of small and long fatigue crack growth behavior in AA 7050-T7451. (15th October 2018) - Bianchetti, C.; Zheng, R.; Chromik, R.R.; Lévesque, M.; Brochu, M.
Highlights: Comparison of small and long crack behavior is proposed for a wide Δ K range. The microstructure of AA7050-T7451 was thoroughly characterized. The recrystallized grain boundary was identified as the microstructural barrier. Transition from closure-free to crack closure behavior was characterized. Crack closure decreased as the crack growth rate threshold neared. Abstract: Fatigue crack growth behaviors of small and long cracks are compared in terms of crack closure, from near-threshold to final fracture, in over-aged aluminum alloy AA 7050-T7451. This is done experimentally to quantify inputs for crack propagation models such as the Navarro-Rios model. Growth rate of small cracks are determined as a function of stress intensity factor range using replicas taken from etched specimens loaded at high and low stress amplitudes. Similar data for long cracks are obtained using a compact tension C(T) specimen. Recrystallized grains are found to be the most significant microstructural barrier to propagation when cracks are small. In addition, small cracks typically appear to behave as closure-free long cracks. Transition from apparent closure-free to crack closure behavior is observed and characterized in terms of grain size. Finally, analysis of crack closure effects on C(T) specimens shows that long cracks propagating in the studied aluminum undergoes roughness- and oxide-induced closure.